Efektifitas Terapi Senam Stroke Terhadap Perbaikan Kemampuan Fungsional Pasien Paska Stroke: The Effectiveness of Stroke Exercise Therapy on the Improvement of Functional Ability in Post-Stroke Patients - Neri Basmara; Reni Prima Gusty; Ema Julita (NERS Jurnal Keperawatan, 2012)
Stroke exercise physical therapy is routinely performed in Dr. M. Djamil Hospital with the purpose of increasing the functional abilities of stroke patients. This study aimed to determine the difference in effectiveness of exercise therapy twice a week and three times a week in improving the functional abilities of stroke patients. The study was conducted for four weeks using a quasi-experimental design with a non-randomized approach without a pretest-posttest control group design. The sample consisted of 22 respondents who experienced ischemic stroke. The instrument used for data collection was a sheet measuring functional ability based on the Barthel index scale. The analyses were performed using the Shapiro-Wilk normality test, paired t-test, and Mann-Whitney test. The results showed that exercise therapy can improve stroke patients' functional ability after stroke, with the mean of therapy exercise stroke twice and three times a week being 9.636 (p=0.000) and 10.909 (p=0.000), respectively. However, the difference in the increase in functional ability between the two groups of participants was not statistically significant (p-value = 0.198). Based on the findings of this study, it is suggested that the management of the department of Dr. M. Djamil Padang establish guidelines for this therapy in the form of SOPs, and that the frequency of stroke therapy be performed as calisthenics three times a week for optimum improvement of functional ability to be felt by patients who follow this therapy.